Os vetores do plano e do espaço e os registros de representação - Castro, Samira Choukri de (2001)
This work fits in the field of investigations on teaching and learning Analytic Geometry. It focuses on the notion of vector. The theoretical basis relied on R. Duval (1995) representation registers and mathematics learning theory. To him, it is essential for the learning process to distinguish representatives and represented, and, thus, for teaching, to take on account the different semiotical representation ways of a same mathematics object. The research comprised the conception, accomplishment, observation and analysis of a didactical sequence, aiming the articulation of vector concept registrations. The application was carried througjh students who had attended or were attending Analytical Geometry and Vectors disciplines. For the sequence elaboration the three registers categories have been considered: the symbolical, the figural and the natural language ones. On the symbolical, n-uplas and linear combinations , on the figural the arrow and on the natural language vector . The preliminary analysis for the sequence elaboration have been produced by a diagnosis test applied to seventy students of three engineering schools. The subjects taking part in the sequence have been defined considering these students characteristics. The results achieved by this research indicate that the students had great difficulties in activities envolving the conversion of vector registrations and that they could improve their knowledge through the application of the sequence, confirming the validity of the theoretical view that has set it up